DNA methylation markers of insulin resistance surrogate measures in the Atherosclerosis Risk in Communities (ARIC) study - Jeewoen Shin; Jan Bressler; Megan L. Grove; Michael Brown; Elizabeth Selvin; James S. Pankow; Myriam Fornage; Alanna C. Morrison; Chloé Sarnowski (Epigenetics)
Insulin resistance (IR) is a risk factor for cardiovascular diseases and type 2 diabetes. Associations between DNA methylation (DNAm) and IR have been less studied in African ancestry (AA) populations than those of European ancestry (EA). We aimed to identify associations between whole blood DNAm and IR in up to 1,811 AA and 964 EA participants from the Atherosclerosis Risk in Communities (ARIC) study. We quantified IR using three surrogate measures: the homeostasis model assessment of insulin resistance (HOMA-IR), the triglyceride-glucose index (TyG), and the triglyceride glucose-body mass index (TyG-BMI). We used ancestry-stratified linear regression models to conduct epigenome-wide association studies of IR, adjusting for batch effects and relevant covariates. Among 484,436 tested CpG sites, 39 were significantly associated with IR, of which 31% (10 in AA and two in EA) were associated with TyG-BMI and not previously reported for IR or related traits. These include a positive association at cg18335991-SEMA7A in AA. SEMA7A inhibits adipogenesis of preadipocytes and lipogenesis of mature adipocytes. DNAm levels at cg18335991 have been reported to be negatively associated with SEMA7A expression in blood. After additionally adjusting for smoking and drinking status, 15 of the 39 significant CpG sites remained significant or suggestive. Our study identified novel IR-associated CpG sites, contributing to a broader understanding of the epigenetic mechanisms underlying IR in diverse populations.